Exploring the emergence and changing dynamics of a new integrated rice-crawfish farming system in China - Yanbing Wei; Daniel Müller; Zhanli Sun; Miao Lu; Huajun Tang; Wenbin Wu (Environmental Research Letters, 2023)
Crop-aquaculture systems are widely adopted around the world as they can provide high protein and energy outputs per unit of land and raise farm incomes, particularly for smallholder farmers. Recently, a new crop-aquaculture system, which combines rice production with crawfish breeding (integrated rice-crawfish farming), has emerged and rapidly expanded in China. However, the spatial extent and temporal dynamics of this integrated farming system largely remain unclear, which prohibits rigorous impact assessments to support its sustainable development. Here we use time series of Landsat satellite data, for the first time, to explore the emergence and the changing dynamics of this rice-crawfish farming system for the period of 2013–2021 in five provinces (8050.167em600 km²) of China, where 90% of the global crawfish are produced. Our analysis reveals that the total area of rice-crawfish farming in these five provinces increased steadily from 0.11 Mha in 2013 to 0.70 Mha in 2019, then sharply contracted by a third in 2020 and rebounded in 2021. Spatially, rice-crawfish system is located primarily in low-elevation plain areas with abundant water resources, where paddy rice cultivation has traditionally dominated agriculture. More concentrated rice-crawfish distribution is observed in Jianghan Plain, and regions around Dongting Lake and Poyang Lake. The spatial distribution of rice-crawfish cultivation experienced considerable expansion towards the east and north from 2013 to 2021, with the largest expansion found in Jiangsu and Anhui after 2018. At the county level, over 6% of counties experienced notable area increases of more than 60 km² from 2017 and 2019, but 20% of counties have decreased from 2019 to 2021. Among the converted land use types, irrigated cropland is the largest contributor to rice-crawfish expansion with a contribution of 56%, followed by water bodies (25%) and rainfed cropland (13%). The spatial and temporal information provided in this study helps to understand the evolution of rice-crawfish cultivation in China and facilitates more efficient management of land resources under the rapid development of this farming system.
Keywords: 320; crop-aquaculture system; crawfish; paddy rice; spatio-temporal dynamics